2020
DOI: 10.3390/plants9070817
|View full text |Cite
|
Sign up to set email alerts
|

Genebank Phenomics: A Strategic Approach to Enhance Value and Utilization of Crop Germplasm

Abstract: Genetically diverse plant germplasm stored in ex-situ genebanks are excellent resources for breeding new high yielding and sustainable crop varieties to ensure future food security. Novel alleles have been discovered through routine genebank activities such as seed regeneration and characterization, with subsequent utilization providing significant genetic gains and improvements for the selection of favorable traits, including yield, biotic, and abiotic resistance. Although some genebanks have implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 195 publications
0
36
0
1
Order By: Relevance
“…Examples of conservation activities that impact on the use of the genetic resources that have been covered in this Special Issue include the following: easy access to genetic resources increases the capacity of breeders to respond to climate change and the availability of appropriate technologies [41]; access to traditional knowledge on the use of wild plant species [27]; a systematic association-mapping of wheat varieties with SNP markers was successfully used to associate adult plant stripe rust resistance with specific rust races, and results can be used in marker-assisted selection [29]; the analysis of a local genetic panel of manna ash with a continental dataset allowed conclusions on the presence of a possible glacial refuge, and thus facilitates the collecting and use of more genetic diversity [38]; the systematic characterization of ancient grape germplasm in Cyprus allowed the discovery of so far unnoticed genetic diversity [35]; literature searches and conducting field surveys allowed the identification of unknown wild food plants in Kenya [20]; fact sheets promoted the use of traditional food plants in the South Pacific [26]; the exploitation of the local genetic diversity of traditional pea landraces in Greece is fundamental for conservation practices and crop improvement through breeding strategies [32]; the evaluation of maize landrace accessions under heat and drought stresses resulted in invaluable sources of genes/alleles for adaptation breeding [30]; the review of recent efforts that build evidence of the importance of wild food plants in selected countries, while providing examples of cross-sectoral cooperation and multi-stakeholder approaches, contributes to enhancing their sustainable use [19]; the advances in conventional and molecular breeding for the drought tolerance of conventional staple crops, and the introduction of drought-tolerant neglected and underutilized species into existing production systems has the potential to enhance the resilience of agricultural production under conditions of water scarcity [40]; the utilization of advanced phenotyping tools, coupled with high-throughput genotyping, will accelerate the use of genetic resources and fast-track the development of more resilient food crops for the future [24]; and genomics-assisted breeding is increasingly facilitating the introgression of favorable genes and quantitative trait loci from wild species into cultigens, and will lead to a wider use of crop wild relatives in the development of resilient cultivars [25].…”
Section: Genetic Resources and Plant Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of conservation activities that impact on the use of the genetic resources that have been covered in this Special Issue include the following: easy access to genetic resources increases the capacity of breeders to respond to climate change and the availability of appropriate technologies [41]; access to traditional knowledge on the use of wild plant species [27]; a systematic association-mapping of wheat varieties with SNP markers was successfully used to associate adult plant stripe rust resistance with specific rust races, and results can be used in marker-assisted selection [29]; the analysis of a local genetic panel of manna ash with a continental dataset allowed conclusions on the presence of a possible glacial refuge, and thus facilitates the collecting and use of more genetic diversity [38]; the systematic characterization of ancient grape germplasm in Cyprus allowed the discovery of so far unnoticed genetic diversity [35]; literature searches and conducting field surveys allowed the identification of unknown wild food plants in Kenya [20]; fact sheets promoted the use of traditional food plants in the South Pacific [26]; the exploitation of the local genetic diversity of traditional pea landraces in Greece is fundamental for conservation practices and crop improvement through breeding strategies [32]; the evaluation of maize landrace accessions under heat and drought stresses resulted in invaluable sources of genes/alleles for adaptation breeding [30]; the review of recent efforts that build evidence of the importance of wild food plants in selected countries, while providing examples of cross-sectoral cooperation and multi-stakeholder approaches, contributes to enhancing their sustainable use [19]; the advances in conventional and molecular breeding for the drought tolerance of conventional staple crops, and the introduction of drought-tolerant neglected and underutilized species into existing production systems has the potential to enhance the resilience of agricultural production under conditions of water scarcity [40]; the utilization of advanced phenotyping tools, coupled with high-throughput genotyping, will accelerate the use of genetic resources and fast-track the development of more resilient food crops for the future [24]; and genomics-assisted breeding is increasingly facilitating the introgression of favorable genes and quantitative trait loci from wild species into cultigens, and will lead to a wider use of crop wild relatives in the development of resilient cultivars [25].…”
Section: Genetic Resources and Plant Breedingmentioning
confidence: 99%
“…With respect to germplasm management, an example of the use of single nucleotide polymorphisms (SNP) markers for the identification of duplicate accessions of Brassica oleracea in genebank collections has been presented [22], while another paper highlights the importance of information management to assist in germplasm and genebank management and to enhance the use of germplasm [23]. Genebank phenomics is a rather novel approach in modern genebanking, and Nguyen and Norton [24] shed light on digital phenotyping methods that enable capturing traits during annual seed regeneration events to enrich genebank phenotypic datasets, thus adding value to crop collections and increasing their usefulness for the identification of traits of interest for breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pre-breeding research can underpin breeding programs by screening genetic resources including wild relatives and landraces available from genebanks for identification of adaptive and tolerance alleles to abiotic stresses [34,51,[70][71][72]. A large reservoir of wild species germplasm is held in genebanks across the world, and proper characterization and evaluation of these genetic resources through phenomic and genomic approaches is imperative to enable the selection of the best crossing parents for breeding [65,67,[73][74][75][76].…”
Section: Explore Wild Relatives and Landraces Available At Grain Genementioning
confidence: 99%
“…The major genetic sources of tolerance to abiotic stresses can come from crop's centers of origin-the geographical regions where plants normally grow under such stressful conditions and can involve using wild relatives as donors of favorable genes. Genebanks around the world hold large reservoirs of genetic material including wild relatives and landraces that needs to be characterized [76], and they should continue to strive to conserve these valuable resources and make them readily available to breeding programs.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…SG maintains a green leaf color with high photosynthesis capacity until late grain-filling stage, especially under drought and heat stress conditions and secures grain yield [31]. Therefore, this trait is potentially important in future breeding programs to develop climate-smart crop varieties [32]. Although SG is most informative in such stress situations, we have observed that ambient temperature at late vegetative and seed maturity stages rose during the last few years and there were large variations in SG, which allowed us to select a few accessions having high SG.…”
Section: Pre-screening For Accelerating Pgr Researchmentioning
confidence: 99%